Sickness presenteeism in the aftermath of COVID-19: Is presenteeism remote-work behavior the new (ab)normal? - Ferreira, A. I.; Mach, M.; Martinez, L.; Miraglia, M. (Frontiers in Psychology, 2022)
Due to the confinement imposed by the COVID-19 pandemic situation, companies adopted remote work more than ever. The rapid rise of remote work also affected local life and many employers introduced or extended their telework activities because of the associated advantages. However, despite the evident positive benefits, some employees were pressured to work remotely while ill. This evidence brought new challenges to the presenteeism literature. This article investigates how individual, economic/societal, and organizational/sectorial/supervisory-related variables can moderate the role of a contagious disease, such as the COVID-19, in explaining presenteeism behavior. Moreover, the current research presents a multi-level conceptual model (i.e., organizational, individual, supervisory factors) to describe how a new construct of remote-work presenteeism behavior mediates the relationship between different post pandemic health conditions (e.g., allergies, back pain, depression, anxiety) and future cumulative negative consequences. The authors suggested that the widespread pervasive adoption of remote work because of COVID-19 has important implications for the presenteeism literature and opens avenues for further research.